Recent advances in utilization of palm kernel cake in poultry - Liang, Juan Boo; Abdullah, N.; I., Zulkifli; Soleimani, A. F. (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Malaysia produces approximately 2.2 million tons of palm kernel cake (PKC) annually. Almost all of this agro-industrial biomass is sold as cattle feed in the EU and other cattle producing countries. In Malaysia, PKC is also used as ruminant feed but the amount used for this purpose is little because of the small ruminant industry. On the other hand, there is an urgent need to find alternative feed ingredients to offset the high importation bills and the over dependence on feed importation based on corn-soybean based diet for the local poultry industry, which is the main source of animal protein (eggs and meat) in Malaysia. Institute of Tropical Agriculture, UPM, has been entrusted with a Long-term Research Grant Scheme (LRGS) program, supported by the Ministry of Education Malaysia to develop strategies to enhance the competitiveness and sustainability of the poultry industry through improved feedstock in Malaysia. Palm kernel cake is the focal feed ingredient of the program. Approaches; including biological treatments using locally developed exogenous enzymes from various microorganisms and physical treatments such as extrusion technology are been studied to improve the feeding values of PKC for poultry. Since bulk of the fiber component of PKC is mannan, our research also focuses on the extraction and utilization of the mannan-oligosaccharides extracts from PKC as prebiotics to replace the use of antibiotics for poultry and other livestock production. This presentation highlights available results of the above mentioned studies.